STRATIFIKASI GASTROPODA DI KAWASAN PESISIR PULAU-PULAU KECAMATAN BULANG - Wahyu Fitriyani; Notowinarto Notowinarto; Lani Puspita (SIMBIOSA, 2013)
Reseach about stratification of Gastropod has been conducted in the open waters of Kecamatan Bulang, Batam, Riau Arcipelago Province. This study aims to determine the type, level species, stratification, and distribution pattern of gastropod in the area. The research showed that there where 16 Gastropod family found in this areas, which consists of 26 spesies. Calculation result between distance with dense of Gastropod index any stratification, that is more of distance with beach so the Gastropod index is less.